1984
DOI: 10.1139/m84-031
|View full text |Cite
|
Sign up to set email alerts
|

Metal binding by the peptidoglycan sacculus of Escherichia coli K-12

Abstract: The peptidoglycan of Escherichia coli K-12 strain AB264 was isolated by treating whole cells with sodium dodecyl sulfate and was purified by deoxyribonuclease, ribonuclease, and trypsin treatment. Like the peptidoglycan of Bacillus subtilis, this peptidoglycan proved able to bind substantial amounts of metallic ions from aqueous solution. In particular, most metals of the transition I series were bound from solution in amounts greater than or equal to 1 mumol/mg dry weight peptidoglycan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 0 publications
3
44
0
Order By: Relevance
“…Bacillus on the other hand showed a better tolerance and uptake with Cd (Graph 5). Similar findings were reported with respect to Cd biosorption studies [3,4]. It was also reported that metal binding capacities of E. coli was relatively higher than Bacillus by [5].…”
Section: Discussionsupporting
confidence: 88%
“…Bacillus on the other hand showed a better tolerance and uptake with Cd (Graph 5). Similar findings were reported with respect to Cd biosorption studies [3,4]. It was also reported that metal binding capacities of E. coli was relatively higher than Bacillus by [5].…”
Section: Discussionsupporting
confidence: 88%
“…Whole-cell pellets were then resuspended in 100 ml 25 mM sodium phosphate buffer (pH 6.0). Insoluble peptidoglycan and associated teichoic acids were extracted using the boiling 4% sodium dodecyl sulfate (SDS) procedure described by Holye and Beveridge (22), taking care to preserve natural levels of O acetylation (9). The SDS-insoluble cell wall material (for convenience referred to below as peptidoglycan) was recovered by ultracentrifugation at 160,000 ϫ g for 55 min at 25°C, washed at least four times with 25 mM sodium phosphate buffer (pH 6.0), and lyophilized.…”
Section: Methodsmentioning
confidence: 99%
“…Two liters of P. aeruginosa PAO1 in TSB was incubated at 37ЊC and 125 rpm to obtain an optical density at 600 nm (OD 600 ) of 1.0. After centrifugation at 5,000 ϫ g for 30 min, the cell pellet was resuspended in distilled water, and murein sacculi were prepared by boiling cells in 4% (final concentration) SDS for 3 h as described previously (13). Murein sacculi were sonicated to homogeneity prior to incorporation into the polyacrylamide gel used in the zymogram system.…”
Section: Bacteriamentioning
confidence: 99%